A New Substrate for Alkaline Phosphatase Based on Quercetin Pentaphosphate - Mwilu, Samuel K; Okello, Veronica A.; Osonga, Francis; Miller, Seth; Omowunmi, A. Sadik (My University, 2014)
We describe the characterization and application of quercetin pentaphosphate (QPP), a new fluorimetric substrate for the detection of alkaline phosphatase (ALP) activity. QPP exhibits major absorbance peaks at 260/ 410 nm and a strong fluorescent at λex/λem = 425/510 nm at alkaline pH. The product of enzymatic reaction between QPP and ALP has a strong absorbance peak at 324 nm with no fluorescence activity at the investigated wavelengths. The product generated from the enzymatic reaction was found to be proportional to ALP activity and ALP activity was monitored by absorbance difference at 310 nm and 410 nm. The change in absorbance was found to be proportional to the ALP concentration with a linear detection range and a limit of detection of 0.01-16 U/L and 0.766 U L-1, respectively. The enzyme activity was also monitored by evaluating the change in fluorescence emission at 530 nm with a linear range of 0.01 – 8 U L-1 and a detection limit of 0.062 U L-1. Further, the validity of the new substrate for ALP in conjugated form was tested using Bacillus globigii spores as model sample. A detection limit of 5998 spores/mL was obtained using QPP as a substrate. Unlike the parent compound, QPP substrate exhibits stability in solution for over three and half months and was stable under storage for over 12 months. The results obtained demonstrate the effectiveness of QPP for ALP and compares well with favorably with other fluorescent substrates such as Fluorescein, Alexsa Fluor and Cy5.
Keywords: Quercetin pentaphosphate; Alkaline phosphatase; Substrate and fluorescence